How sport specialization age and training components influence the achievements of elite athletes - Novan, Novrizal Achmad; Mulyana, Boyke; Syihab, Syifa Fakhomah; Nuryadi, Nuryadi; Risjanna, Masayu Rizka (Jurnal Keolahragaan, 2024)
Early specialization in sports for young elite athletes was undertaken for a variety of positive reasons, but it also can lead to increased vulnerability to injury, burnout, limited skill development, and negative effects on mental well-being as a result of intense training from a young age. The purpose of this study was to determine the relationship between age of sport specialization and training components to the achievements. This was a correlational survey and a cross-sectional approach to elite athletes in the city of Bandung. The sample for this study consisted of 84 high-level athletes who competed in 27 different sports and were eligible for athlete incentives from the government. Athletes were surveyed using a questionnaire to answer questions about their debut age, training frequency, duration, intensity, and highest championship achievement. The results of bivariate analysis showed that age, gender, age of specialization, duration of exercise, and intensity of exercise were not related to sports achievement. Based on the results of statistical analysis, it was known that the frequency of exercise was significantly correlated with sports achievement. Compared to athletes who train less than five times per week, athletes who train more than five times per week were found to have higher performance. Future possible research will assist in identifying the success factors of young athletes who begin sports specialisation at a young age.